A Cross-Sectional Study of factors associated with prevalence and progress of Dentin Hypersensitivity - Jabeen, Wajeeha; Qazi, Sakina; Malik, Saman; Haider, Syed Shahan; Farooq, Muhammad; Hafeez, Resham (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: DHS is a prevalent dental disorder. Several variables affect DHS to analyze the problems prevalence and correlations. Place of study: Dental College (HITEC-IMS), Taxilla Duration of Study: February 2019 to August 2021 Methods: This cross-sectional investigation looked at 182 surgical dentistry patients at (HITEC-IMS) Dental College, Taxilla. Demographic and associated variables were accumulated from a survey and one examiner looked at clinical linkages. A visual analog scale was devised to categorize the results (VAS). Chi-Square test was used to examine the related factors at the significance level of 0.05. Results: Described data is shown. The Chi-Square test was employed here with 0.05 for all variables. DHS was found in 26% of the cases. Hard toothbrushes, traumatic occlusion, gingival surgery history, and horizontal brushing (P <0.0002, P <.004) are all associated with DHS (P<.0004). Conclusion: According to the results, high awareness about DHS and its associated factors are mandatory for better prognosis.